Developing and Evaluating an Educational Game to Support Early Reading Skills in Kindergarten Students - Juwiantho, Hans; Rafael, Angelo Brian; Liliana, Liliana; Sari, Lily Eka (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Reading is a crucial skill that should be learned from an early age, as it plays a vital role in daily life. While most children can easily learn to read, some struggle with the process. Therefore, effective learning media are needed to support children's reading development. This study develops and evaluates an educational game to assist young children in learning to read. Unlike previous studies, the game integrates multiple interactive modes that reinforce word recognition, spelling, and sentence construction through auditory and visual cues. The game features a simple user interface, a collection of 100 open vocabulary words, and three gameplay modes designed to support different aspects of early reading skills. The game's effectiveness was assessed through an experiment involving 12 kindergarten students, divided into a game-playing and a non-game-playing group. The findings indicate that the educational game can enhance kindergarten students' reading skills. Moreover, the game increases students' enthusiasm and motivation for learning to read. However, further improvements, such as additional features and platform expansion, are necessary to make the game more accessible to a broader audience.